2017
DOI: 10.1523/eneuro.0354-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Wortmannin Attenuates Seizure-Induced Hyperactive PI3K/Akt/mTOR Signaling, Impaired Memory, and Spine Dysmorphology in Rats

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 40 publications
4
13
0
Order By: Relevance
“…The progressive deterioration of hippocampal‐dependent trace memory that we found complements studies that have found impairments in contextual memory, spatial memory, and cued recall of amygdala‐dependent memory in delay fear conditioning following an acute seizure . In addition, our follow‐up trace fear conditioning experiments expand on previous studies, which have only examined memory as far out as 40 h after a seizure and indicate that memory impairment persists up to 2 weeks.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The progressive deterioration of hippocampal‐dependent trace memory that we found complements studies that have found impairments in contextual memory, spatial memory, and cued recall of amygdala‐dependent memory in delay fear conditioning following an acute seizure . In addition, our follow‐up trace fear conditioning experiments expand on previous studies, which have only examined memory as far out as 40 h after a seizure and indicate that memory impairment persists up to 2 weeks.…”
Section: Discussionsupporting
confidence: 79%
“…There is one study by Carter et al, 2017, that has provided evidence that inhibition of the upstream regulator of mTOR, PI3K, reduces long‐term memory deficits. Inhibiting PI3K 10 min after a seizure by wortmannin leads to a reduction in downstream phospo‐Akt, phospho‐S6 (ser240/244), and a partial rescue of long‐term auditory memory, but no effect on long‐term contextual memory . The lack of full rescue in Carter et al, 2017, may indicate a role for FMRP, which we found to be altered, in seizure‐induced memory impairment.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Previous studies have demonstrated that aberrant alterations in the dendritic spine density are commonly observed in brain samples from epilepsy patients and epilepsy animal models (Jiang et al, 1998;Wong and Guo, 2013). Dendritic spine abnormalities might increase the hyperexcitable circuits or intrinsic properties of neurons that might cause seizures, and seizures also result in damage to dendrites and dendritic spines, which might contribute to progressive recurrent seizures, mental disorders, memory disturbances, and other neurological deficits in epilepsy patients (Jimenez-Mateos et al, 2015;Awad et al, 2016;Carter et al, 2017) Previous study suggest that KIF1A mutations that cause hereditary spastic paraplegia are loss-of-function mutations that decrease motility (Esmaeeli Nieh et al, 2015). However, not all mutations are loss-of-function.…”
Section: Discussionmentioning
confidence: 99%
“…Class I catalytic isoforms are the most commonly studied class of PI3Ks and are termed p110α, -β, -γ, and -δ (Vanhaesebroeck et al, 2010). While Class I p110-kinases have been predominantly investigated in the context of cancer and the immune system (Vanhaesebroeck et al, 2016), recent research demonstrates an emerging role for PI3K signaling in neurological function, with direct roles for PI3Ks having been identified in axon extension (Cosker and Eickholt, 2007), dendritic complexity, and synaptogenesis (Jaworski et al, 2005;Kumar et al, 2005;Martín-Peña et al, 2006;Cuesto et al, 2011;Jordán-Álvarez et al, 2012Jordán-Álvarez et al, , 2017Carter et al, 2017). Nevertheless, the role of individual PI3K isoforms in these processes and their contribution to neurological disorders is largely unknown.…”
Section: Introductionmentioning
confidence: 99%